In the memory of the European scientist (sketches to the biography of Vasyl N. Skrypka – a folklorist, a literary critic, a teacher, a social and cultural leader of the twentieth century) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
This article is about a folkloristic heritage of V. M. Skrypka, his comparative researches into theory and history of Slavonic folk-lore.
Keywords: heritage; folklore